Spatial statistical analysis of infrastructure systems in Calgary, Alberta. Issue 11 (19th September 2019) - Hawkins, Jason; Kattan, Lina; Hettiaratchi, Joseph Patrick; Taron, Joshua; Assefa, Getachew
Abstract : In this paper, the consumption of various infrastructure systems in Calgary, Alberta by residential, commercial, and industrial sectors is considered. Statistical models are developed to quantify the influences of built form factors, in addition to traditional factors of sociodemography. Analyses are performed by census community for electricity, transportation by mode of travel, and demolition permits by their size and frequency. The employment of a common methodology in a single geography allows for comparison across infrastructure systems and determination of common patterns. Assessing total consumption does not necessarily lead to a consistent interpretation. By differentiating electricity consumption by sector and transportation by mode, consistent analysis can be conducted that identifies the correct relationships. We find a trend toward increasing consumption of electricity use moving out from the center of the city, but also an increasing reliance on the private automobile.